(untitled) (Journal of Tropical Pharmacy and Chemistry, 2012)
Ketoconazole is an antifungal azole synthetic which derivatived from imidazole. Ketoconazole is practically insoluble in water and its bioavailability depend on pH condition of the gastrointestinal tract. The purpose of the research is to increase the solubility of ketoconazole by solid dispersion method using Eudragit® E 100, PEG 6000, and glycerol. Solid dispersion was evaluated with respect to solubility, cristalinity, complexation and morphology of solid dispersion. The optimum formulation with the highest solubility was resulted by solid dispersion with ratio ketoconazole - Eudragit® E 100 - glycerol of 1:8:0.5. X-ray diffraction test revealed the change of crystalline ketoconazole and similar to Eudragit® E 100. This result was also supported by spectrum of infrared and endothermic peak of differential scanning calorimetry. Based on scanning electron microscopy morphology of pure Eudragit® E 100 and solid dispersion was similar. Solid dispersion of ketoconazole with Eudragit® E 100 and glycerol improved solubilty.